EÂ·voiution of Topology and Wei,ght-s. of Neural NetwoÂ·rks. Using.Semi Genetic Operators - Yous-if, 1. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
EvolutionaryÂ·co.nipimit'iQo  is  aÂ· c'!a s of glbbal Â·searb  techniqbased on the lei.lffi:ing process ,of  g po_pl)'latiog-Â·of pote.n:tiaf solutions toa  ven probl_e-ID'.  thahas .been  succe_ssfull'y  applied    19  v ety ofprQblern, lll thls paper a riew approach  to. design lie_ ural ne'twQj:ksbased oh ev.ohltipnary -computa.tio.rt iÂ·s pre.Seri-L  _A   tine-f.!Â£ clurP.mosome'repr:esentati:on  or the etwor}< i_s.  u_secl: 'Q.y  genetiC  gperntb_l:s, whicQallow thÂ¢  voJution of.the   chitecture and' weight-s Â·simMltaneousfywithout the neÂ¢d : tlocal Â·-v.:e!gh_t-sÂ· opthnization. Dii$ , paper - d- cribes.t he approach, the" o.per HQ(S and rep 'H:tS  r  \llt$  '()[the a}Jplicati:on :Qfthis te6hnique-.to- ;;everal  biAal)l cl'iissifiÂ·cation prob eros